Patterns of pharmacotherapies used to treat alcohol use disorders: A populationbased administrative data study. (2018) - Nickel, Nathan; Leong, Christine; Prior, Heather; Konrad, Geoffrey; Bolton, James; MacWilliam, Leonard; Ekuma, Okechukwu; Paille, Michael; Valdivia, Jeff
No abstract available